Systemic risk spillovers in the European banking and sovereign network - Frank Betz; Nikolaus Hautsch; Tuomas A. Peltonen; Melanie Schienle (Goethe University Frankfurt, Center for Financial Studies (CFS), 2014)
We propose a framework for estimating network-driven time-varying systemic risk contributions that is applicable to a high-dimensional financial system. Tail risk dependencies and contributions are estimated based on a penalized two-stage fixed-effects quantile approach, which explicitly links bank interconnectedness to systemic risk contributions. The framework is applied to a system of 51 large European banks and 17 sovereigns through the period 2006 to 2013, utilizing both equity and CDS prices. We provide new evidence on how banking sector fragmentation and sovereign-bank linkages evolved over the European sovereign debt crisis and how it is reflected in network statistics and systemic risk measures. Illustrating the usefulness of the framework as a monitoring tool, we provide indication for the fragmentation of the European financial system having peaked and that recovery has started.
Keywords: G01; G18; G32; G38; C21; C51; C63; 330; systemic risk contribution; tail dependence; network topology; sovereignbank linkages; Value-at-Risk